PENGARUH LIKUIDITAS, LEVERAGE, FIRM SIZE, DAN STRUKTUR MODAL TERHADAP KINERJA KEUANGAN - Sari Ayu Awal; Viriany Viriany (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
In this study, the purpose is to determine the effect of liquidity, leverage, firm size, andalso capital structure on the financial performance of manufacturing companies. For the sample of this study amounted to arround 185 manufacturing companies, there is have on the Indonesia Stock Exchange (IDX) during the period of 2017-2019, and alsousing the purposvie sampling method, also with the application program named of Eviews-12. The final test result of this study indicate that liquidity and capital structurehave a significant and negative effect on financial performance. Meanwhile, leverageand firm size do not have effect on financial performance.